First report of Acutaspis oliveirai (Lepage & Giannotti, 1942) (Hemiptera: Diaspididae) in Central Brazil: occurrence on Myrsine guianensis (Aubl.) Kuntze (Primulaceae) in the Brazilian Cerrado - Marcelo T. Castro; Sandro C. L. Montalvão; Vera R. S. Wolff (Entomological Communications, 2024)
Recent research shows that the Cerrado has a great diversity of scale insects (Insecta: Hemiptera: Coccomorpha) in association with native plants. This work aimed to report the occurrence of Acutaspis oliveirai (Lepage & Giannotti, 1942) (Hemiptera: Diaspididae) found for the first time in Central Brazil and in plants of Myrsine guianensis (Primulaceae), a common species in the Brazilian Cerrado, that has potential for use in landscaping and the recovery of degraded areas. This is the first report of the occurrence of A. oliveirai in a native plant of the Cerrado biome and in the Central Brazil. Acutaspis oliveirai individuals were found on the leaf surface of M. guianensis leaves in two locations in the Federal District, Brazil, causing irregular yellowing and chlorotic spots throughout the leaf blade.